The Influence of Firm Characteristics and Capital Structure on Sustainable Growth Rate: Moderating Effect of Industry Sector - Muh Afdhal Mubarak A S; Slamet Haryono (Master of Management, School of Business and Management, Petra Christian University, 2023)
This study examines the impact of firm characteristics and capital structure on the sustainable growth rate of technology and consumer goods companies listed on JII, considering the moderating influence of industrial sector variables. The research utilizes secondary panel data sourced from annual financial reports. The population consists of JII-listed companies from 2018 to 2022, with a purposive sampling approach resulting in a sample size of six firms. The Structural Equation Modeling - Partial Least Square analysis findings reveal that firm size, characteristics, and capital structure significantly influence the sustainable growth rate, with firm size further enhanced through industrial sector moderation. The study contributes theoretically by emphasizing the significance of firm characteristics and capital structure while offering practical insights by showcasing how firms can stimulate sustainable growth through enhanced profitability and capital structure, thereby facilitating reinvestment and development.